RELIGION AND IT’S FUNCTION IN HUMAN LIFE - Elihami, Elihami; Suriani, Suriani (Al-Mirah: Jurnal Pendidikan Islam, 2020)
Religion is a very important necessity for humans, whether we realize it or not, every human being definitely needs religion. Humans are weak human beings. this is proven by limited human reason. so that every human needs the all-sumptuous essence to be used as a place to complain all his anxiety. Islamic religion is a religion perfecting previous religions. The sources of Islamic law are Al Qur'an, Al Hadith, and Al Ijtihad.